Morphometric and structural diagnosis of fault reactivation in the Cenozoic: A case study of the Blumenau-Soledade Lineament in southern Brazil - Salamuni, Eduardo (2021)
The hypothesis that geomorphometric parameters and structural-geological features are diagnostic of reactivation of the Blumenau-Soledade Lineament in central-western Santa Catarina, Brazil was tested by confronting data on asymmetry, elongation, morphological markers, drainage patterns, and river anomalies of the Pelotinhas catchment and structural data for the Serra Geral Group (Paraná Basin). The results indicate reactivation of the lineament as a dextral strike-slip fault, as the cause of an associated morphostructure characterized by an escarpment along the left bank of the river as well as being responsible for catchment asymmetry and morphometric anomalies. Although fault data indicate paleostress correlatable to regional tectonic events described in the literature, we propose that the earliest paleostress pulse possibly was active during the Paleocene-Eocene transition, with σ1 oriented NE-SW and σ3 NW-SE. In the early Paleogene, the stress system evolved as an extensional pulse. During the Paleogene and early Neogene, the paleostress field rotated with reorientation of the σ1 axis between NNW and NNE. The current tectonic regime was established between the Late Pleistocene and Holocene, with compressional stress σ1 oriented approximately WNW-ESE and σ3 NNE-SSW, as it generally occurs in the South American Plate.